2020
DOI: 10.1080/21870764.2020.1725259
|View full text |Cite
|
Sign up to set email alerts
|

Chemical design of lightweight aggregate to prevent adhesion at bloating activation temperature

Abstract: The purpose of this study is to control the viscous behavior of lightweight aggregates through the chemical design of a lightweight aggregates material in order to solve the problem of the adhesion of lightweight aggregates by viscous behavior in the bloating activation temperature range of lightweight aggregates. In order to induce a reduction of Fe 2 O 3 inside the aggregates, Fe 2 O 3 and carbon were added to acid clay so as to produce aggregate. The particle density and the water absorption rate of the agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Leismann [10], for example, used literature data to determine the phase proportions of natural clays that are favourable for bloating behaviour, as shown in Table 1. The most important gases produced during bloating are released between 850 and 1150 °C from the decomposition of the flux components Fe2O3, CaCO3, CaMg(CO3)2, CaSO4 and FeS2 [18,19]. These bloating gases are O2, CO2, CO, H2O, N2, SO2 and H2.…”
Section: Theory Of Bloatingmentioning
confidence: 99%
See 3 more Smart Citations
“…Leismann [10], for example, used literature data to determine the phase proportions of natural clays that are favourable for bloating behaviour, as shown in Table 1. The most important gases produced during bloating are released between 850 and 1150 °C from the decomposition of the flux components Fe2O3, CaCO3, CaMg(CO3)2, CaSO4 and FeS2 [18,19]. These bloating gases are O2, CO2, CO, H2O, N2, SO2 and H2.…”
Section: Theory Of Bloatingmentioning
confidence: 99%
“…These bloating gases are O2, CO2, CO, H2O, N2, SO2 and H2. According to Hoffmann [14], the organic carbon content also has an important influence on The most important gases produced during bloating are released between 850 and 1150 • C from the decomposition of the flux components Fe 2 O 3 , CaCO 3 , CaMg(CO 3 ) 2 , CaSO 4 and FeS 2 [18,19]. These bloating gases are O 2 , CO 2 , CO, H 2 O, N 2 , SO 2 and H 2 .…”
Section: Theory Of Bloatingmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that both iron phases enhanced the bloating process, which was linked to pore formation in the lightweight aggregate. Wie et al [ 8 ] investigated clay mixtures with different percentages of activated carbon and Fe 2 O 3 . Again, the results indicated that Fe 2 O 3 reduction appeared to be a key factor in producing the lightweight aggregate, in which case it was necessary to add more than 5 wt.% of iron along with percentages higher than 2 wt.% of activated carbon.…”
Section: Introductionmentioning
confidence: 99%